Epidemiological patterns of traumatic brain injury identified in the emergency department in Ontario, 2002-2010. (3rd June 2015) - Fu, T; Jing, R; Cusimano, M
Abstract : Background: Traumatic brain injury (TBI) is the leading cause of traumatic death and disability, and most TBIs are treated in the Emergency Department (ED). We examined the incidence and epidemiological patterns of TBIs presenting to Ontario EDs over an eight-year period. Methods: All TBI-related ED visits between April 2002 and March 2010 were identified using a population-based database that is mandatory for ambulatory care facilities in Ontario. Incidence rates were reported across multiple strata, including age group, sex, and mechanism of injury. Results: From 2002-2010, there were 1, 032, 249 ED visits for TBI in Ontario. Peak rates occurred among young children ages 0-4 (349 per 10, 000) and elderly adults ages 85+ (243 per 10, 000). Overall, males experienced a 53% greater rate of TBI compared to females. Falls (47%), motor vehicle crashes (MVC; 10%), and sports-related injuries (9%) were the most common causes of TBI. The highest rates of TBI-related falls, MVCs, and sports-related injuries occurred among young children (0-4) and elderly adults (85+), adolescents/young adults (15-24), and children (5-14), respectively. Conclusions: Our study reveals a substantial health system burden associated with TBI in the ED setting, underscoring the need for enhanced surveillance and prevention efforts targeted to vulnerable demographic groups.